(untitled) (American Journal of Islam and Society, 2006)
This panel discussion, held on 27 June 2006 and sponsored by the Council on American-Islamic Relations (CAIR), featured James Yee, a 1990 West Point graduate and Muslim chaplain assigned to Camp Delta (Guantanamo Bay) and attorney Gene Fidell of Feldesman, Tucker, Leifer, and Fidell, who has worked on cases involving Guantanamo Bay inmates. The discussion took place at the Rayburn House Office Building in Washington, DC. After making opening remarks on illegal immigrants and terrorism, Mohammad Nimer (research director, CAIR) introduced Chaplain Yee, who had served at Camp Delta from November 2002 to September 2003. While there, he experienced the detention center’s living conditions and received awards and recognition for his service. On 10 September 2003, however, he was arrested and accused of espionage, aiding the enemy, mutiny, and sedition. Eventually, he was locked up alongside enemy combatants Yasser Hamdy and Jose Padilla in a naval brig in South Carolina. Later, all charges were dropped, including unrelated charges regarding national security. Yee explained his role as advocating for the free exercise of worship. He advised the camp commander on religious aspects of prison operations and listened to prisoners’ complaints and concerns, including authorized and unescorted access to the cells. In addition, he observed detainee treatment and made recommendations. He described two operations: detention operations run by military police or guards (e.g., providing them with clothes) and intelligence gathering, which included extracting information. Yee was assigned to the former group, as the commanding general at the time, Major General Geoffrey Miller, considered it unethical for the chaplain to be present during intelligence gathering operations ...